Studentsâ Environmental Awareness and Practices: Basis for Development of Advocacy Program - Cruz, Jenny P (EDUCARE, 2016)
ABSTRACT: Environmental degradation has been a problem, which needs to be address to meet sustainability. It is important to consider the balance between human activity development and environmental protection requires a sharing of responsibilities that can be equated with the behaviour towards the environment and natural resources. Preservation of the environment is one of the concerns of the Philippines government through the DENR (Department of Environment and Natural Resources). However, it will be a great help if every citizens will be involved most especially the youth. There are some studies conducted about environmental preservation with different outcomes, such as modified environmental awareness scale; development of lesson exemplars; modular package on environmental awareness protection and conservation, etc. Aiming to produce an environmental advocacy program, this study was conducted to promote the environmental awareness of the students through active participation in the different environmental programs and activities through the joint effort of the participating schoolâs organization. The descriptive method of research was used in this study, which looked into the environmental awareness and practices of the selected fourth year high school students in the Philippines. The instrument of EAS (Environmental Awareness Scale) was modified to give emphasis on the environmental problems and issues evident at present. Findings of the study were the basis for development of an environmental advocacy program.KEY WORDS: Environmental Awareness; High School Students in the Philippines; Environmental Awareness Scale; Environmental Practices; Advocacy Program.About the Author: Jenny P. Cruz is a Teacher at the Santa Elena High School, W.C. Paz Street., Santa Elena, Marikina City, Philippines; and an Alumna of PNU (Philippine Normal University), in which she has graduated last April 2015. For academic interests, the author is able to be contacted via e-mail at: arthurpnu@yahoo.comHow to cite this article? Cruz, Jenny P. (2016). âStudentsâ Environmental Awareness and Practices: Basis for Development of Advocacy Programâ in EDUCARE: International Journal for Educational Studies, Vol.9(1), August, pp.29-40. Bandung, Indonesia: Minda Masagi Press owned by ASPENSI, ISSN 1979-7877. Chronicle of the article: Accepted (February 22, 2016); Revised (June 30, 2016); and Published (August 30, 2016).